2015
DOI: 10.1287/mksc.2014.0900
|View full text |Cite
|
Sign up to set email alerts
|

Product and Pricing Decisions in Crowdfunding

Abstract: This paper studies the optimal product and pricing decisions in a crowdfunding mechanism by which a project between a creator and many buyers will be realized only if the total funds committed by the buyers reach a specified goal. When the buyers are sufficiently heterogeneous in their product valuations, the creator should offer a line of products with different levels of product quality. Compared to the traditional situation where orders are placed and fulfilled individually, with the crowdfunding mechanism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
159
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(180 citation statements)
references
References 30 publications
0
159
4
1
Order By: Relevance
“…In addition, the creator's own backing history-that is, the number of projects that the project creator has backed-has been found to be significant [54]. Funding goal [22,37] Project creator Social network [37,52] Backing history [30,54] Presentation Visualization [30,31] Description [51,53] Communication Updates [37,51] Posts and comments [31,37] Rewards Number of rewards [31,51] Pricing [26,51] Presentation refers to the use of texts, images, and videos to describe and advertise projects. Videos and images have been found to positively influence fundraising success [30,31], and the depth of the project description has been identified as another success factor [51].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the creator's own backing history-that is, the number of projects that the project creator has backed-has been found to be significant [54]. Funding goal [22,37] Project creator Social network [37,52] Backing history [30,54] Presentation Visualization [30,31] Description [51,53] Communication Updates [37,51] Posts and comments [31,37] Rewards Number of rewards [31,51] Pricing [26,51] Presentation refers to the use of texts, images, and videos to describe and advertise projects. Videos and images have been found to positively influence fundraising success [30,31], and the depth of the project description has been identified as another success factor [51].…”
Section: Related Workmentioning
confidence: 99%
“…While some researchers have found that the number of rewards influences the chances of fundraising success [e.g., 31], the design of reward menus, including the selection of reward tiers and the donation amounts connected to them, has largely been neglected. Xiao et al provided first evidence that comparably high-priced rewards positioned at the end of the choice set lead to significantly higher success rates [51], and Hu et al argued that, given two product options of similar quality but at different prices, buyers with high product valuations prefer the high-priced option, as long as they perceive that other buyers may have low product valuations [26]. Still, even though researchers have started to explore crowdfunding success from the viewpoint of the reward menu's design, we know little about how rewards, and how they are presented, influence crowdfunding success.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, crowdfunding allows companies to better exploit their market potential (Belleflamme et al, 2010;Hu et al, 2014). Belleflamme et al (2010) and Hu et al (2014) show in a theoretical model that reward-based crowdfunding (pre-ordering) allows for price discriminations.…”
Section: Legal Analysis Jobs Actmentioning
confidence: 99%
“…Belleflamme et al (2010) and Hu et al (2014) show in a theoretical model that reward-based crowdfunding (pre-ordering) allows for price discriminations.…”
Section: Legal Analysis Jobs Actmentioning
confidence: 99%